Subregional effects of meniscal tears on cartilage loss over 2 years in knee osteoarthritis. Issue 1 (12th August 2010) - Chang, Alison; Moisio, Kirsten; Chmiel, Joan S; Eckstein, Felix; Guermazi, Ali; Almagor, Orit; Cahue, September; Wirth, Wolfgang; Prasad, Pottumarthi; Sharma, Leena
Abstract : Objectives: Meniscal tears have been linked to knee osteoarthritis progression, presumably by impaired load attenuation. How meniscal tears affect osteoarthritis is unclear; subregional examination may help to elucidate whether the impact is local. This study examined the association between a tear within a specific meniscal segment and subsequent 2-year cartilage loss in subregions that the torn segment overlies. Methods: Participants with knee osteoarthritis underwent bilateral knee MRI at baseline and 2 years. Mean cartilage thickness within each subregion was quantified. Logistic regression with generalised estimating equations were used to analyse the relationship between baseline meniscal tear in each segment and baseline to 2-year cartilage loss in each subregion, adjusting for age, gender, body mass index, tear in the other two segments and extrusion. Results: 261 knees were studied in 159 individuals. Medial meniscal body tear was associated with cartilage loss in external subregions and in central and anterior tibial subregions, and posterior horn tear specifically with posterior tibial subregion loss; these relationships were independent of tears in the other segments and persisted in tibial subregions after adjustment for extrusion. Lateral meniscal body and posterior horn tear were also associated with cartilage loss in underlying subregions but not after adjustment for extrusion. Cartilage loss in the internal subregions, not covered by the menisci, was not associated with meniscal tear in any segment. Conclusion: These results suggest that the detrimental effect of meniscal tears is not spatially uniform across the tibial and femoral cartilage surfaces and that some of the effect is experienced locally.